Effect of ascorbic acid and chloroquine diphosphate on the quality and fertility of - CHEEDE, G S; PANGAONKAR, G R; SINGH, JAGIR (The Indian Journal of Animal Sciences, 2011)
The present investigation was carried out to assess the effect of ascorbic acid, an antioxidant and chloroquine diphosphate, a membrane stabilizer, on the quality and fertility of buffalo bull semen. Neat, post equilibrated and post thawed semen with additives (ascorbic acid @ 0.02% or chloroquine diphosphate @ 10–5M) and without additives (control) was subjected to microscopic examination for percent individual motility, live sperms count and head abnormalities. Healthy, normal cycling buffaloes (62) were inseminated with post-thaw semen with ascorbic acid (n=21), chloroquine diphosphate (n=22) and without additives (n=19). Semen extended with additives had significantly higher individual motility and live sperm. The overall conception rate was 42.1, 57.14 and 54.54% with control, ascorbic acid or chloroquine diphosphate fortified semen, respectively. It is concluded that supplementation of ascorbic acid or chloroquine diphosphate to extender improved the semen quality and fertility of buffalo bull semen.